The critical discourse analysis on Joe Biden’s elected president speech - Try Mahendra Siregar (Politeknik Negeri Bali, 2021)
This research discusses critically Joe Biden’s elected president speech on 8 November 2020. The research objectives are the discourse structure and the ideologies contain in Biden’s speech. The research designed is qualitative descriptive which the data source is in form of documentation that is an online transcription of Joe Biden’s speech. The technique to analyze the data, the researcher adopted six CDA steps; problem identification, literature specification, development of code analysis, content analysis and coding, reading and interpretation, and explaining findings. The theory to analyze the speech is Van Djik’s Critical Discourse Analysis Elements; namely macrostructure, microstructure, and superstructure. By applying the CDA elements, the researcher found discourse structures those are macrostructure (thematic)-intertextually, microstructure in two main focused semantics (background, detail, and presupposition), syntaxes analysis (cohesion; who, and, so, etc. and pronoun; I, you, they, we, etc.), stylistic (pronoun; related to certain contexts and lexicon selection to show speakers emphasizes) and rhetoric in term of persuasive function. Then superstructures of the speech are opening, content, and closing remark. The other importance of this research finding is the ideologies stated implicitly and explicitly by Biden, which are unity, equality, and freedom for the US citizens.